[Laiškas] / Kučevskis A. - Adomui Zavadskiui. - (:unkn) unknown (My University, 1855)
1 laiškas apie lietuviškų knygų atsiuntimą.
Keywords: Rankraščiai; Laiškai; Autografų kolekcija; Zawadzki, Adam, 1814-1875; Kučevskis, A.